2007
DOI: 10.1007/s10803-006-0322-8
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Donepezil in Enhancing Learning and Memory in Special Populations: A Review of the Literature

Abstract: This review discusses the laboratory and clinical research supporting the rationale for the efficacy of donepezil (Aricept USA) in enhancing cognition in autism, Alzheimer disease, Down syndrome, traumatic brain injury, Attention Deficit Hyperactivity Disorder (ADHD), and schizophrenia. While preliminary animal models have shown effective, human studies exclusive of Alzheimer disease are sparse. Although attention and memory are unlikely a sole operation of the cholinergic system, evidence indicates a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 117 publications
1
23
0
Order By: Relevance
“…Systemic administration of the drug in the BTBR mouse model of autism improved cognitive flexibility, comparable to the results obtained in spatial reversal learning tests after administration of Donepezil in doses similar to the current study (Yoo et al, 2007). In addition, our results in the social novelty test of untreated BTBR mice agrees with a previous report (Moy et al, 2007), in which these mice spent significantly more time in the chamber containing the novel stranger, but not in physical contact with it.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Systemic administration of the drug in the BTBR mouse model of autism improved cognitive flexibility, comparable to the results obtained in spatial reversal learning tests after administration of Donepezil in doses similar to the current study (Yoo et al, 2007). In addition, our results in the social novelty test of untreated BTBR mice agrees with a previous report (Moy et al, 2007), in which these mice spent significantly more time in the chamber containing the novel stranger, but not in physical contact with it.…”
Section: Discussionsupporting
confidence: 91%
“…Similar effects were achieved by direct microinjection into the dorsomedial striatum but not into the ventomedial-striatum. The effect of the AChEI Donepezil on cognitive functions was previously examined extensively on neurotypical mice and rats or animal models of Alzheimer disease (Yoo et al, 2007), but, to our knowledge, never on ASD animal models. For example, the positive behavioral effect of the drug was shown with respect to attention, learning, and memory (reviewed in (Yoo et al, 2007)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chez et al (2003) also documented gains on measures of expressive and receptive language as well as core ASD features (using the Childhood Autism Rating Scale) in a double-blind study of 43 children who were placed on a 2.5 mg/day dose of donepezil. However, the results were equivocal, as betweengroup statistical analyses were not conducted and the placebo group evidenced greater improvement on some measures than those on active medication (Yoo et al 2007). Niederhofer et al (2002) reported the results of a double-blind, placebo-controlled crossover trial of galantamine with 20 children with ASD.…”
Section: Introductionmentioning
confidence: 99%